Mediterranean diet related metabolite profiles and cognitive performance. Issue 2 (February 2023) - Papandreou, Christopher; Papagiannopoulos, Christos; Koutsonida, Myrto; Kanellopoulou, Afroditi; Markozannes, Georgios; Polychronidis, Georgios; Tzakos, Andreas G.; Fragkiadakis, Georgios A.; Evangelou, Evangelos; Ntzani, Evangelia; Tzoulaki, Ioanna; Aretouli, Eleni; et al.
Summary: Background & aims: Evidence suggests that adherence to the Mediterranean diet (MedDiet) affects human metabolism and may contribute to better cognitive performance. However, the underlying mechanisms are not clear. Objective: We generated a metabolite profile for adherence to MedDiet and evaluated its cross–sectional association with aspects of cognitive performance. Methods: A total of 1250 healthy Greek middle-aged adults from the Epirus Health Study cohort were included in the analysis. Adherence to the MedDiet was assessed using the 14-point Mediterranean Diet Adherence Screener (MEDAS); cognition was measured using the Trail Making Test, the Verbal Fluency test and the Logical Memory test. A targeted metabolite profiling (n = 250 metabolites) approach was applied, using a high-throughput nuclear magnetic resonance platform. We used elastic net regularized regressions, with a 10-fold cross-validation procedure, to identify a metabolite profile for MEDAS. We evaluated the associations of the identified metabolite profile and MEDAS with cognitive tests, using multivariable linear regression models. Results: We identified a metabolite profile composed of 42 metabolites, mainly lipoprotein subclasses and fatty acids, significantly correlated with MedDiet adherence (Pearson r = 0.35, P-value = 5.5 × 10 −37 ). After adjusting for known risk factors and accounting for multiple testing, the metabolite profile and MEDAS were not associated with the cognitive tests. Conclusions: A plasma metabolite profile related to better adherence to the MedDiet was not associated with the tested aspects of cognitive performance, in a middle-aged Mediterranean population.